How to develop young physical activity leaders? A Delphi study. - Isobel P Steward; Emma S Young; Sufyan Abid Dogra; Elizabeth Stamp; Andy Daly-Smith; Kammy Siddique; Kelly Morgan; Jamie Crowther; Jennifer Hall; JU:MP research & development team (PLoS ONE)
The International Society for Physical Activity and Health advocates for increased capability of the physical activity workforce as a key ingredient to a system-based approach. Young leader programmes are gaining traction globally as peers are a primary influence on young people and positive role models are important for increasing or maintaining physical activity. Yet, there is limited understanding of 'what works' for training young physical activity leaders. This study aims to develop a consensus on how to identify and support young people to become physical activity leaders. An iterative three-phased mixed methods Delphi consensus approach. A rapid review focused on the feasibility, acceptability and impact of existing young leader physical activity training (phase one); focus groups (n = 3) and interviews (n = 6) with 15 practitioners and young leaders to examine young physical activity leader training needs (phase two); and a three-round questionnaire process (phase three). Stakeholders (n = 43) from across the public, voluntary and education sectors, academics and young leaders completed all questionnaires. A consensus was reached for 75 statements related to: young leader traits prior to and following training, recruitment methods, training content, delivery format and context, relationships, incentives, and skill development. The Delphi process, combining insight from multi-sectoral stakeholders, identified a range of factors that underpin young leader training programmes. These factors should be applied to develop a curriculum and comprehensive training programme to provide young leaders with the required capability to be effective within their roles, and ultimately support an increase in physical activity amongst children and young people.